2021
DOI: 10.5194/egusphere-egu21-6633
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Probabilistic seismic hazard maps for California do not perform better relative to historical shaking data when site-specific VS30 is considered

Abstract: <div> <p>Probabilistic seismic hazard assessments forecast levels of earthquake shaking that should be exceeded with only a certain probability over a given period of time are important for earthquake hazard mitigation. These rely on assumptions about when and where earthquakes will occur, their size, and the resulting shaking as a function of distance as described by ground-motion models (GMMs) that cover broad geologic regions. Seismic hazard maps are used to develop building code… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Although using the median hazard instead of the mean improves the fit (M0 is reduced by 10%), a substantial misfit remains. Similarly, Gallahue (32) found that using the median hazard for California reduced the discrepancy between the models and data by only about 10%, and Salditch (33) found that median hazard models for France reduced the discrepancy by 14%.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although using the median hazard instead of the mean improves the fit (M0 is reduced by 10%), a substantial misfit remains. Similarly, Gallahue (32) found that using the median hazard for California reduced the discrepancy between the models and data by only about 10%, and Salditch (33) found that median hazard models for France reduced the discrepancy by 14%.…”
Section: Discussionmentioning
confidence: 97%
“…Because the main contribution to the PSHA results used for building codes is typically from above-average ground motions, current GMICEs lead to overestimation of the expected intensity. Correcting for this bias in the GMICE in California substantially reduces the discrepancy, indicated by a decrease of the M0 metric of 40 to 70% (32). Because a similar bias will occur in GMICEs developed for different regions using the same standard methodology, improved conversion equations will likely reduce the discrepancy between hazard models and data elsewhere.…”
Section: Discussionmentioning
confidence: 99%